Maternal and foetal outcomes of preeclampsia and eclampsia patients in a tertiary level hospital in Delhi - Punyatoya Bej; Pragti Chhabra; Arun Kumar Sharma; Kiran Guleria (Wolters Kluwer Medknow Publications, 2015)
Background: Preeclampsia and eclampsia (PE) are diseases that occur due to pregnancy.PE affects the mother and foetal health throughout pregnancy. This leads to poor outcome of mother and newborn in the postpartum period. This study determined the maternal and foetal outcomes of preeclampsia and eclampsia patients from a tertiary level hospital were determined. Methods: One hundred twenty two women of preeclampsia or eclampsia, delivered beyond 22 weeks of gestation were allocated as cases. Simultaneously 122 women were selected as controls with no diagnosis of preeclampsia or eclampsia. The study was designed as a case control study. Foetal and maternal outcome of pregnancy was asked by using a pre-tested questionnaire. The data was collected from over two year period and statistically analyzed. Results: The percentages of preeclampsia and eclampsia cases were 2.54%and 0.79% respectively during the study period. Proportion of preterm deliveries was more in PE patients (32.0%) than controls (27.9%). Intra uterine death and still birth were reported more among PE cases (7.8% and 3.8% respectively) than controls (1.6% and 0.8% respectively). Two neonatal deaths were reported among PE cases. Incidence of low birth weight babies was more in PE cases (55.4%) than controls (43.1%). Bad obstetric history reported more in PE cases (30.3%) than controls (22.1%). Conclusion: Adverse foetal outcome in the form of intrauterine death, still birth, low birth weight, preterm delivery and neonatal deaths were observed more among PE cases. Bad obstetrics history was detected more in PE cases.